2016
DOI: 10.1371/journal.pone.0162571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Theileria lestoquardi Antigens Recognized by CD8+ T Cells

Abstract: As part of an international effort to develop vaccines for Theileria lestoquardi, we undertook a limited screen to test T. lestoquardi orthologues of antigens recognised by CD8+ T lymphocyte responses against T. annulata and T. parva in cattle. Five MHC defined sheep were immunized by live T. lestoquardi infection and their CD8+ T lymphocyte responses determined. Thirteen T. lestoquardi orthologues of T. parva and T. annulata genes, previously shown to be targets of CD8+ T lymphocyte responses of immune cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…A low degree of serological cross-immune reactivity has been detected between T. ovis and T. lestoquardi together with the relatively long duration of a detectable antibody response 17 , but it is unclear whether this provides cross protection against disease. There is evidence that immunity to T. lestoquardi in sheep involves T cell mediated responses 18 against the macroschizont infected leukocyte and similar immune responses have been reported for T. annulata and T. parva 19 . Genetic and antigenic similarities are evident for T. lestoquardi and T. annulata, and cross-immunity between the two species has been demonstrated 17,20 .…”
Section: Discussionsupporting
confidence: 64%
“…A low degree of serological cross-immune reactivity has been detected between T. ovis and T. lestoquardi together with the relatively long duration of a detectable antibody response 17 , but it is unclear whether this provides cross protection against disease. There is evidence that immunity to T. lestoquardi in sheep involves T cell mediated responses 18 against the macroschizont infected leukocyte and similar immune responses have been reported for T. annulata and T. parva 19 . Genetic and antigenic similarities are evident for T. lestoquardi and T. annulata, and cross-immunity between the two species has been demonstrated 17,20 .…”
Section: Discussionsupporting
confidence: 64%
“…The present study represents the first broad population genetic analysis of T. lestoquardi in Sudan using seven micro-and mini-satellite markers of T. annulata (Weir et al, 2007). Biological and molecular phylogenetic studies clearly indicated that T. lestoquardi is more closely related to T. annulata than to T. parva Schnittger et al, 2003, Goh et al, 2016. Both species were probably evolved from a common ancestor and this fact is supported biologically such as both parasites share the same vector tick.…”
Section: Discussionsupporting
confidence: 58%
“…AH-1 cells were re-suspended to a concentration of 1 × 10 5 ml in PBS supplemented with 0.05 % (w/v) NaN 3 (Sigma-Aldrich), 5% ΔHFBS (flow buffer), and stained for viable cells using the Live/Dead® Fixable Violet Dead Cell Stain (Invitrogen, Thermo Fisher Scientific) prior to labeling with the ovine MHC class I specific monoclonal antibody (mAb) IL-A88 at a 1:2 dilution of hybridoma tissue culture supernatant (14). This antibody has previously been shown to bind surface expressed recombinant ovine MHC class I on transfected COS-7 cells (15).…”
Section: Methodsmentioning
confidence: 99%